(untitled) (Medical Forum Monthly, 2024)
Objective: To study the arterial supply of motor areas of human brain regarding its variable source due to its significance in neurosurgical practice and angiography. Study Design: It is prospective descriptive study on cadaveric human brains Place and Duration of Study: This study was conducted on different cadaveric brains collected from anatomy and Forensic Departments of various teaching institutes during July2007-July2008 Materials and Methods: A total 100 brains were collected. skull cap was cut by electric saw meinges were saved, Skull cap was removed. Brain was removed through epidural space without any injury to blood vessels. After putting one week in 10 % formaline jar, dura was removed and branula No.24 was passed into each anterior and middle cerebral arteries separately at different times. Blue Indian ink was injected into anterior cerebral artery after ligating anterior communicating Artery. After injection branula was removed and ligature applied to the artery so that dye may not escape. Now branula was passed into middle cerebral Artery and the red Indian ink was injected so that contrasting colours clearly demarcate the blood vessels supplying the motor areas of brain. Arteries supplying from functional areas were divided in two groups A and B. Group A include primary motor cortex and group B include motor speed area or Broca's area. Each of this group is further subdivided into three sub groups A1, A2 , A3 and B1, B2, B3. Sub group A1 and B1 include area supplied by single artery, Sub group A2 and B2 include area supplied by multiple arteries whereas subgroup 3 include variant arteries supplying that area. Results were statistically evaluated. Sign test was used to test for presence of variant artery in each area and it was statistically significant. Results: In group A out of 100 cases no case fell in such group A1 , 96 cases (96%) fell in such group A2, where middle cerebral Artery and anterior cerebral Artery supplying the area . The frontal branches of middle cerebral artery two to three in number and anterior parietal branch of middle cerebral Artery supply 80% of area while one to two branches of frontopolar Artery, branch of anterior cerebral Artery supply 1.0 to 1.5 cm strip on supero medial surface of motor area. The anterior cerebral Artery supply the leg area and middle cerebral Artery the face trunk and upper limb area. In sub group A3, 4 cases (4%) accessory middle cerebral Artery appeared as variant Artery. In group B out of 100 cases 90 cases (90%) fell in sub group B1. 9 cases (9%) fell in sub group B2 where middle cerebral Artery through frontal branch and accessory middle cerebral Artery supply the area 1 case (1%) fell in such group B3. Where anterior temporal branch of inferior trank of middle cerebral Artery supply the area as variant Artery. 19 cases out of 100 (19%) showed variations among these 4 cases (4%) showed variations in arterial supply of primary motor cortex and 1 case (1%) showed variations in the arterial supply of motor speech area. Collateral vessels may modify the effects of cerebral ischaemia. Conclusion: anatomical variations of the cerebral arteries are of immense importance in surgery , angiography and all non-invasive procedures to help in interpretation of cranial angiogram. The major variations include duplication segmental duplication, aplasia, hypoplasia and fenestration of the vessels.